2005
DOI: 10.1111/j.1348-0421.2005.tb03709.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Typhoid Carriers among Blood Donors and Patients with Biliary, Gastrointestinal and Other Related Diseases

Abstract: Enteric fever due to Salmonella Typhi is a major public health problem. Typhoid carriers have high titres of Vi agglutinins in their sera. We worked out the baseline data for Vi agglutinins from 705 healthy blood donors (controls) by ELISA and compared it with 446 patients with biliary, gastrointestinal and other related diseases (cases). The samples were divided into five groups based on the disease condition of the patients from whom they were collected. Group A (n = 196) consisted of patients with stones in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 8 publications
(6 reference statements)
5
31
0
Order By: Relevance
“…Sterility is partially maintained by the secretion of IgA and mucus, preventing bacterial survival and adhesion to the surface of the lumen and the major bile duct, respectively [15]. Here, we found a wide array of organisms in the bile of individuals undergoing cholecystectomy, some of which have been previously isolated from the gallbladder [16]–[18]. Again, whether these organisms functionally stimulate cholecystitis or cholelithiasis, or merely have the ability to colonize damaged gallbladders, remains unclear.…”
Section: Discussionmentioning
confidence: 88%
“…Sterility is partially maintained by the secretion of IgA and mucus, preventing bacterial survival and adhesion to the surface of the lumen and the major bile duct, respectively [15]. Here, we found a wide array of organisms in the bile of individuals undergoing cholecystectomy, some of which have been previously isolated from the gallbladder [16]–[18]. Again, whether these organisms functionally stimulate cholecystitis or cholelithiasis, or merely have the ability to colonize damaged gallbladders, remains unclear.…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, potential risk factors may be confounded by the fraction of the population with gallbladder abnormalities [37]. For instance, the risk of becoming a chronic carrier following an acute infection increases with age, is greater for women than for men, and is particularly associated with cholelithiasis and cholecystitis [10, 38]. …”
Section: Epidemiology and Treatment Of Chronic Carriagementioning
confidence: 99%
“…Some species of bacteria, like salmonella typhi is in association with gall bladder cancer (Vaishnavi et al, 2005), streptococcus bovis and colon cancer , and chlamydia pneumonia reported with lung cancer (Kuper et al, 2000).…”
Section: Introductionmentioning
confidence: 99%